Pengaruh model pembelajaran cooperative integrated reading and composition (circ) terhadap keterampilan membaca aksara jawa pada peserta didik kelas v sekolah dasar - Meisya Ika Puspitaningrum; Joko Daryanto; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2025)
This study aims to assess whether the Cooperative Integrated Reading and Composition (CIRC) instructional model affects the ability of read Javanese script among V grade students. This study uses a quasi-experimental method with a pretest-posttest control group design. The experimental group receives treatment using the CIRC model, while the control group is taught using the NHT model. This research is quantitative and involves a sample of 73 students. The sample of class V students obtained from the Ahmad Yani group was then grouped into an experimental class and a control class. Data collection was conducted through an oral test of reading Javanese script, with instrument validity assessed using Aiken’s V and instrument reliability tested using Cronbach's alpha. Data analysis and prerequisite testing included normality tests, homogeneity tests, and balance tests. The hypothesis was tested using an independent sample t-test with a significance level of 0.050. The results of this study can be concluded that there is an influence of the CIRC learning model on Javanese script reading skills which is shown by the results of the calculation of tvalue 3,036 > ttable 1,994, then it is rejected, meaning that there is an influence of the CIRC learning model on Javanese script reading skills in class V students.